Foundations of Mandatory Vaccination and Its Sanctions in Iran and the West (With Emphasis On Covid-19) - Mohammad Bagher Moghaddasi; zahra ameri; ahmad khosravi (پژوهش تطبیقی حقوق اسلام و غرب, 2022)
Vaccination plays a significant role in fighting diseases especially during epidemics. With the spread of epidemics such as Covid-19, the debate over compulsory vaccination is largely get around whether the creation of a public good takes precedence over the individuals' freedoms? And in the case of the acceptance of compulsion, which mechanisms can be manipulated to ensure it? The results of this research, which has been conducted through a descriptive-analytical-comparativemethod, demonstrate that the opponents of mandatory vaccination, relying on the prohibition of violating the right to life due to side effects of the vaccine and violation of right to privacy as well as emphasizing the individuals' freedom of conscious choice, maintain that the duty of states is only to try to provide the facilities which save the lives of the individuals and not compel them to comply with these attempts. However, advocates of compulsory vaccination, while defending the concept of public health as a public good and its priority over the protection of individual rights, put emphasis on the collective nature of right to health and present a variety of criminal and administrative sanctions in order to force the vaccination. Many western countries have adopted policies within this requirement by diversifying their various administrative and financial sanctions. In Iran, however, the lack of a legal system to provide adequate administrative sanctions particularly in the area of deprivation of social rights and access to public services, as well as encouraging mechanisms, can be an obstacle to ensuring this public interest.